Perilaku Masyarakat Perkotaan Dalam Membuang Sampah Di Bantaran Sungai Bone Di Kelurahan Talumolo, Kecamatan Dumbo Raya - Radjak, Sri Rahmawati M.; Rahmatiah, Rahmatiah; Hatu, Dewinta Rizky R. (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2023)
Environmental pollution is a serious issue in the Talumolo Village at present, as the community's concern for environmental conservation has declined. In the daily lives of the Talumolo Village residents, many activities consciously threaten and disrupt environmental sustainability, one of which is the habit of indiscriminate waste disposal. This behavior leads to the accumulation of garbage that pollutes the body of the Bone River. The research aims to understand the behavior of urban communities in disposing of waste on the banks of the Bone River in the Talumolo Village, Dumbo Raya District, Gorontalo City. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The research results indicate that: First, waste management in the Talumolo Village community is still simple, based on knowledge of managing waste by collecting and burning it to reduce the accumulation of waste on the banks of the Bone River. Second, the emergence of littering behavior on the banks of the Bone River in the Talumolo Village is a result of the failure of one of the functions of the government system, namely providing facilities and infrastructure such as trash bins in the local community. Third, the emergence of the community's littering behavior on the banks of the Bone River is associated with four stages of the community behavior formation process: low public knowledge about waste management, inadequate facilities and infrastructure, imitation of the community in littering on the banks of the Bone River, and government appeals and prohibitions to the local community. Fourth, the impact of the community's littering behavior on the banks of the Bone River causes the river to appear dirty, become a breeding ground for diseases, and contribute to flooding disasters